2000
DOI: 10.1099/00221287-146-10-2521
|View full text |Cite
|
Sign up to set email alerts
|

Secreted products of a nonmucoid Pseudomonas aeruginosa strain induce two modes of macrophage killing: external-ATP-dependent, P2Z-receptor-mediated necrosis and ATP-independent, caspase-mediated apoptosis

Abstract: A nonmucoid clinical isolate of Pseudomonas aeruginosa, strain 808, elaborated ATP-dependent and ATP-independent types of cytotoxic factors in the growth medium. These cytotoxic factors, active against macrophages, were secreted during the exponential phase of growth in a complex medium. Commensurate with the appearance of the cytotoxic activities in the cell-free growth medium, several ATP-utilizing enzymic activities, such as adenylate kinase, nucleoside diphosphate kinase and 5'-nucleotidase (ATPase and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
75
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 30 publications
4
75
0
1
Order By: Relevance
“…In addition, the protein is predicted to be glycosylphosphatidylinositol-anchored and the observed molecular mass of ϳ62 kDa (C-terminal half, spots 40, 41, 42,) and ϳ52 kDa (N-terminal half, spots 60,63,65,69) fit to a predicted 127.6 kDa for the full-length protein (including signal peptide and anchor peptide). Based on sequence comparisons, both halves may very well encode an active serine protease, thereby classifying the full-length protein as a polyprotein.…”
Section: Variation In and Validation Of Vaccine Candidates Hc15 Hc24mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the protein is predicted to be glycosylphosphatidylinositol-anchored and the observed molecular mass of ϳ62 kDa (C-terminal half, spots 40, 41, 42,) and ϳ52 kDa (N-terminal half, spots 60,63,65,69) fit to a predicted 127.6 kDa for the full-length protein (including signal peptide and anchor peptide). Based on sequence comparisons, both halves may very well encode an active serine protease, thereby classifying the full-length protein as a polyprotein.…”
Section: Variation In and Validation Of Vaccine Candidates Hc15 Hc24mentioning
confidence: 99%
“…Nucleoside diphosphate kinase (NDK) (spot 157) is responsible for maintaining the levels of intracellular nucleotide pools but is also involved in cell growth, differentiation, and tumor metastasis (66). A secreted form has been found only in some bacteria (67)(68)(69) and in the nematode Trichinella spiralis (70). A function is suggested by observed ATP-dependent cytotoxicity for macrophages and mast cells and prevention of cells from apoptosis (67,71).…”
Section: Variation In and Validation Of Vaccine Candidates Hc15 Hc24mentioning
confidence: 99%
“…Chakrabarty and others [4,[8][9][10][11] have demonstrated that many pathogenic microorganisms release enzymes that modulate levels of NTPs. Of particular interest is extracellular ATP (eATP), which is expected to accumulate at the site of inflammation [12][13][14], important in immunity against microbial infection.…”
Section: Introductionmentioning
confidence: 99%
“…ATP-binding to P2X 7 receptors of macrophages results in their cytolysis in vitro via necrotic [23,24] or apoptotic pathways [25,26], dependent presumably on the duration of exposure to eATP [27,28]. Extracellular pathogenic bacteria, such as Pseudomonas aeruginosa [10,18], have evolved strategies to avoid phagocytic activity of macrophages by releasing enzymes that increases the level of eATP, thereby triggering apoptosis of these and other professional phagocytes. In contrast, intracellular parasites, like Leishmania spp., are expected to develop strategies in the opposite direction by releasing eATP-utilizing enzymes, thereby prolonging the survival of their host cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation